Demographic Variables and Marital Aggrandizement in Monterrey - Moral de la Rubia, José (Pensando Psicología, 2016)
Introduction: Marital aggrandizement is a tendency to idealize one’s partner. It is considered to be a functional trait correlated to satisfaction with the relationship. There is a scale for its assessment created in Canada (18 items) and adapted in Mexico (14 items), but is not validated. Objectives: 1) To describe the distribution of the Marital Aggrandizement Scale in its original format of 18 dichotomized items (MAS) and its version of 14 ordinal items (MAS14), checking which is better suited to the concept of functional trait; and 2) to study the relationship of MAS and MAS14 with sociodemographic and religiosity (belief and practice) variables, verifying the substantiation of these correlates in controlling the effect of satisfaction with the relationship. Methodology: MAS, Relationship Assessment Ratio (RAS), and a sociodemographic data questionnaire were applied to 431 women and 376 men married or cohabiting in Monterrey, Mexico. Probability sampling of random routes was used. Results: MAS show deviation from normality with positive asymmetry and flattened profile. MAS14 showed slight deviation from normality with slight negative asymmetry and mesokurtic profile. MAS and MAS14 were independent or exhibited low associations with sociodemographich and religiosity variables. Only correlations with religiosity were significant and nontrivial after biasing the effect of satisfaction with the relationship (RAS). Conclusions: The distribution of MAS14 is more consistent with the concept of functional feature it intends to measure and does not require differential scales for sociodemographic variables.